2019
DOI: 10.3389/fevo.2019.00351
|View full text |Cite
|
Sign up to set email alerts
|

The Art of Diplomacy in Vocally Negotiating Barn Owl Siblings

Abstract: To resolve conflicts over limited resources, animals often communicate about their motivation to compete. When signals are transient, the resolution of conflicts may be achieved after an interactive process, with each contestant adjusting its signaling level according to the rival's behavior. Unfortunately, the importance of the real-time signal adjustment in conflict resolution remains understudied, especially using experimental approaches. Here we developed a novel "automatic interactive playback" that inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In addition, more empirical studies are clearly needed on a range of species to understand the generality of the patterns highlighted here. Beside their ubiquity in many taxa, acoustic signals are particularly amenable to fine experimental research using playbacks and continuous recordings, including automatic interactive playbacks (Ducouret et al, 2019) and playbacks targeting specific individuals (e.g., Hinde and Kilner, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, more empirical studies are clearly needed on a range of species to understand the generality of the patterns highlighted here. Beside their ubiquity in many taxa, acoustic signals are particularly amenable to fine experimental research using playbacks and continuous recordings, including automatic interactive playbacks (Ducouret et al, 2019) and playbacks targeting specific individuals (e.g., Hinde and Kilner, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Most remarkably, in the barn owl (Tyto alba), a series of original experiments by Dreiss, Roulin, and collaborators has revealed the vocal negotiation occurring between siblings, before parents bring a single indivisible prey back to the nest (Roulin and Dreiss, 2012). They have shown that owlets challenge each other vocally in an interactive process by adjusting their calls to those of their siblings, either intensifying or reducing begging calls depending on their level of need (Roulin et al, 2009) and their opponents' vocalisations (Ducouret et al, 2019). The most vocal chick in parent's absence is more likely to get the next prey from the parents (Roulin et al, 2009), whilst others refrain from begging to the parents (Dreiss et al, 2010).…”
Section: Post-hatch Vocal Negotiation and Cooperation Between Siblingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although between two feeding events and in the short-term (e.g., about several minutes) the need for resources of each participant does not vary, the negotiation process is still very dynamic, being sensitive to the social interaction process itself. Accordingly, barn owl siblings adjust their vocal negotiation to one another on a short-term basis, independently of variation in food need, as shown by observational and experimental studies [ 27 , 31 , 32 , 33 ]. The negotiation process between siblings may be similar to human dialogues, with specific turn-taking rules being used to decide when an individual will start or stop calling [ 31 , 32 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…When an individual starts calling, it gradually produces longer but fewer calls per minute. When it “relaxes” and makes shorter calls, with longer pauses, another sibling is likely to interrupt it by emitting short calls and can gradually monopolize the negotiation [ 31 , 32 , 34 ]. By following these turn-taking rules, individuals have the opportunity to alternatively signal their motivation and perceive the motivation of their counterparts, which allows each individual to adequately decide to withdraw from the contest or to pursue competitive interaction [ 31 , 32 , 34 ].…”
Section: Introductionmentioning
confidence: 99%